Elaphoglossum clathratum sp. nov. (Dryopteridaceae) from the eastern side of the Andes in Ecuador. (20th March 2013) - Matos, Fernando B.; Moran, Robbin C.
<x xml:space="preserve">Abstract</x> Elaphoglossum clathratum F. B. Matos & R. C. Moran sp. nov. (Dryopteridaceae), which grows at middle elevations on the eastern side of the Andes in Ecuador, is described, illustrated, and compared to its most similar species. It is unusual in Elaphoglossum by having lamina margin scales that are strongly clathrate. Research on the phylogeny of the genus has shown that the new species belongs to Elaphoglossum sect. Polytrichia. However, it is unique in the subulate‐scaled clade of Elaphoglossum by having planar, not subulate, scales.